The Improvements of Teachers Understanding of the Introduction to the Transition Early Childhood Education (PAUD) to Elementary School (SD) Enjoyable Through Optimizing the Merdeka Mengajar Platform (PMM) - Nita Priyanti; Rizki Megawati; Euis Agung Sari; Debora Pujo Widiati; Patimah; Olliviani Elen Komalig (Journal of Educational Science Learning and Research, 2024)
Early Childhood Education (PAUD) has an important role in forming a child's foundation before entering elementary school (SD). The transition from PAUD to SD requires deep understanding from teachers and the government. The implementation of the Merdeka Mengajar Platform (PMM) is considered as a potential implementation to increase this understanding. This research aims to explore efforts to increase understanding of the PAUD-SD transition through PMM implementation and its impact on the various parties involved. Using a qualitative approach, data collection techniques use observation, interviews, documentation. This research involved partners such as IGTKI, HIMPAUDI, PKG, teachers, supervisors and the South Tangerang city education office. Intensive training is given to teachers, while PMM is implemented in PAUD learning. Results show increased understanding and positive collaboration. PMM implementation is effective in creating a pleasant PAUD-SD transition experience. Recommendations include continued training, and regular evaluation. This study contributes to understanding the application of PAUD-SD Transition technology in early childhood education. The results of this research show that there are efforts to make the PAUD-SD transition enjoyable, as evidenced by three targets for change, namely: (1) PPDB does not use calistung tests but uses assessments. (2) MPLS activities have been implemented for 2 weeks. (3) The learning process in developing children's foundational abilities has been carried out in a fun way